Forest Utilization Pattern of Local People: A Study of Sewar Bansbot Village of Dang - K.C., Ganga (Historical Journal, 2020)
This article explores the utilization pattern of forest products. Forest is one of the most important natural resources that have directly benefitted the rural people continuously. The people of study area are dependent on forest for the essential elements of fodder, firewood and timber. The economic role of forests in human life is also valuable. The objectives of this article are to describe the forest utilization pattern and to find out how the local people consume the different forest products respectively as their needs. In the study area firewood is the principal source of energy for cooking and heating until now days. The consumption of firewood depends on the size of family member and utilization purpose. Fodder is very important for livestock raising. Leaves, green twigs and small plants are needed for livestock as their diet. Local people in the study area consume Sotar in order to obtain high volume of compost manure for agriculture. Some people deposit green leaves into the compost pit for decomposition, which is converted into the organic manure. And farmers use this manure in their crop fields according to the requirements. It is mainly depend on the livestock size and availability of the bedding materials in the surroundings. Cattle are strictly prohibited in the entire area of Ban to graze.